The influence of principal inclusive leadership and teacher efficacy on teachers’ innovative behaviour - Dongxiao, Mo; Abdul Kadir, Suhaida; Mohd Sufian Kang, Enio Kang; Hassan, Roshafiza (Human Resource Management Academic Research Society, 2023)
China's education system must continue to innovate in order to keep pace with the development of information technology and globalization, and teacher innovation is a prerequisite for innovation in the education system. Therefore, it is necessary to understand the factors that influence teachers' innovative behavior. This study aims to explore the influence of principal inclusive leadership and teacher efficacy on teachers' innovative behaviors in China's junior high school. We sampled 671 teachers in junior high schools in Guangxi, China. The study found that teachers' perceptions of principal inclusive leadership and teacher efficacy were at high levels and teacher innovative behavior was at medium levels. Principal inclusive leadership dimensions were moderately and positively correlated with teacher innovative behavior. Teacher efficacy dimensions were strongly and positively related to teacher innovative behavior. Both principal inclusive leadership and teacher efficacy had a significant effect on teachers' innovative behavior, accounting for 40.6 of the variance in teachers' innovative behavior. The results of the study indicate that teachers' innovative behavior is not sufficient. Both principal inclusive leadership and teacher efficacy had an impact on teachers' innovative behavior. Therefore, stakeholders should consider principal inclusive leadership and teacher efficacy factors when drafting and implementing policies and programs to improve teachers' innovative behavior.